INVESTIGATION OF THE TiO2 NANOPARTICLES EFFECT ON SEED GERMINATION CHARACTERISTICS OF ZIZIPHORA CLINOPODIOIDES LAM. - Azimi, Reyhaneh; Kianian, Mohammad Kia; Pessarakli, Mohammad (Plant Breeding and Seed Science, 2019)
Improvement in the rate and amount of germination of seeds has a very important effect on the establish-ment of primary seedlings and the increase of rangeland production. The rapid and uniform germination of seeds leads to the successful establishment of plants. The use of nanoscale materials can help germinate faster seeds. Therefore, in this study, the effects of TiO2 nanoparticles in concentrations of 0, 10, 20, 30, 40, 60 and 80 mg / l on the rate and speed of seed germination of Ziziphora clinopodioides Lam. paid. This design was carried out in a completely randomized design with four replications for 20 days at a constant temperature of 20°C under 12 hours of light and 12 hours of darkness at the Germinator of Natural Resources Faculty of the Ferdowsi University of Mashhad. The results showed that germination percentage of treated seeds with TiO2 nanoparticles increased to 23% ppm compared to control treatment. Also, in other concentrations of other nanoparticles, there was a positive effect on speed and germination percentage, so that the effect of different concentrations of nanoparticles on germination characteristics of Ziziphora clinopodioides Lam. seeds was significant. The highest germination percentage was observed in the concentration of 30 ppm and the lowest germination rate at 30 and 20 ppm concentrations. In high concentrations of TiO2 nanoparticles, no positive effects were observed on the germination characteristics of seed Ziziphora clinopodioides Lam. To conclude the use of TiO2 nanoparticles can be improved by improving the seed germination properties of the medicinal plant Ziziphora clinopodioides Lam. that cause increases plant’s establishment in natural areas.